EXPLORING THE ANTECEDENTS OF PRO-ENVIRONMENTAL BEHAVIOR OF BANK EMPLOYEES IN AN EMERGING MARKET: A CONCEPTUAL FRAMEWORK - Ali, A.R.S. Ibn; Rahman, Md. Hasanur; Haque, A S M Ahsanul; Nahar, Shamsun (American International Journal of Multidisciplinary Scientific Research, 2023)
In this modern era, it needs to maintain an auspicious future for the employees to stay in the competitive market for achieving goals of an organization. The main goal of this study was to seek the influencing factors such as environmental commitment, environmental consciousness, environmental ethics, and green human resource management of the pro-environmental behavior of bank employees in the emerging market. The banks are the credential source of the economy of a nation which assists in the growing economy of a country where the employees are the key asset for operating the organization. In this study, various sources have been used to find out the influencing factors of pro-environmental behavior. Based on the extensive literature environmental commitment, environmental consciousness, green human resource management and environmental ethics have a high impact on the pro-environmental behavior of bank employees nowadays also, this study is descriptive and qualitative in nature. For exploring factors data have been collected from secondary sources like various previously published manuscripts and journals namely, Springer database, Scopus indexing database, ABDC database, Google Scholar, Emerald database, ABS, and the profile of banking activities. Based on the discussion of this study the bank management should focus on green human resource management practices and processes for creating encouragement among the employees in terms of achieving organizational objectives. This study will help the management, and policymakers of an organization to prepare and maintain policies and strategies for the pro-environmental behavior of employees for efficient work in the working place especially in bank industries in Bangladesh.JEL Classification Codes: M120, M1.